2003
DOI: 10.1085/jgp.200308888
|View full text |Cite
|
Sign up to set email alerts
|

The Ca-activated Cl Channel and its Control in Rat Olfactory Receptor Neurons

Abstract: Odorants activate sensory transduction in olfactory receptor neurons (ORNs) via a cAMP-signaling cascade, which results in the opening of nonselective, cyclic nucleotide–gated (CNG) channels. The consequent Ca2+ influx through CNG channels activates Cl channels, which serve to amplify the transduction signal. We investigate here some general properties of this Ca-activated Cl channel in rat, as well as its functional interplay with the CNG channel, by using inside-out membrane patches excised from ORN dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
195
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(222 citation statements)
references
References 64 publications
24
195
2
1
Order By: Relevance
“…In contrast to Ano -/-mice, Cnga2 -/y mice have severely impaired olfaction (refs. 25,30 and present work).We conclude that CNG-mediated cation currents do not need an additional boost from anion currents for near-physiological levels of olfactory sensitivity.Although fluid-phase EOGs revealed a significant difference between the genotypes, the ~40% reduction of Ano2 -/-EOG amplitudes is much less than expected from the published 80-90% contribution of Cl -to OSN receptor currents 8,11,12 . The contribution of Ca 2+ -activated Cl -channels was often estimated from the inhibition by NFA 11,37 , but this compound also modulates several other ion 8 channels (for example, refs.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…In contrast to Ano -/-mice, Cnga2 -/y mice have severely impaired olfaction (refs. 25,30 and present work).We conclude that CNG-mediated cation currents do not need an additional boost from anion currents for near-physiological levels of olfactory sensitivity.Although fluid-phase EOGs revealed a significant difference between the genotypes, the ~40% reduction of Ano2 -/-EOG amplitudes is much less than expected from the published 80-90% contribution of Cl -to OSN receptor currents 8,11,12 . The contribution of Ca 2+ -activated Cl -channels was often estimated from the inhibition by NFA 11,37 , but this compound also modulates several other ion 8 channels (for example, refs.…”
mentioning
confidence: 54%
“…After first publications had shown that Ca 2+ -activated Cl -currents could powerfully amplify olfactory receptor currents [4][5][6][7] , this concept has received support from many groups. Experiments with isolated receptor neurons [4][5][6]8 showed that up to 80-90% of the receptor current is carried by Cl -. An important role for Cl -in olfaction was also inferred from EOGs 11,16,37 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations